(untitled) (Research, Society and Development, 2020)
The objective was to determine the carbohydrate quality index (CQI) of the diet of prostate cancer survivors, checking if there is an association with their nutritional status. This is a cross-sectional study, in which socio-demographic, anthropometric and food consumption data were collected from 106 male prostate cancer survivors. The CQI was determined as recommended in a specific protocol. The association between CQI and nutritional status (body mass index - BMI and waist circumference - WC) was assessed by Spearman’s correlation test, with p <0.05 as the significance level. The average CQI was 12 (3.3). There were 50 (47.1%) overweight patients and 44 (41.5%) with elevated WC. There was no correlation between IQC and BMI (p = 0.647), nor with WC (p = 0.425), but among the CQI components, some significant correlations were detected. The CQI emerges as an appropriate and quick tool to assess the diet in relation to following international nutritional guidelines for the prevention of prostate cancer. Future studies may define which score reflects adequate adherence to cancer preventive nutritional recommendations.